Athlete's Heart in Asian Military Males: The CHIEF Heart Study - Liu, Pang-Yen; Tsai, Kun-Zhe; Lima, Joao A. C.; Lavie, Carl J.; Lin, Gen-Min (Frontiers in Cardiovascular Medicine, 2021)
Background: Elite athlete’s heart is characterized by a greater left ventricular mass indexed by body surface area (LVMI) and diastolic function; however previous studies are mainly conducted in non-Asian athletes compared to sedentary controls. Methods: This study included 1,388 male adults, aged 18-34 years, enrolled in the same unified 6-month physical training program in Taiwan. During the midterm exams of 2020, all trainees completed a 3-kilometer run (endurance) test, and 577 were randomly selected to attend a 2-minute push-up (muscular strength) test. Elite athletes were defined as the performance of each exercise falling one standard deviation above the mean (16%). Cardiac structure and function were measured by echocardiography and compared between elite and non-elite athletes. Multiple logistic regression analysis was used to determine the independent predictors of elite athlete status at each exercise modality. Results: As compared to non-elite controls, elite endurance athletes had greater LVMI (84.4±13.6 g/m2 vs. 80.5±12.9 g/m2, p <0.001) and lateral mitral E’/A’ ratio (2.37±0.73 vs. 2.22±0.76, p <0.01) with lower late diastolic A’ (7.77±2.16 cm/sec vs. 8.30±3.69 cm/sec, p =0.03). Elite strength athletes had greater LVMI (81.8±11.4 vs. 77.5±12.1, p =0.004) and lateral mitral E’/A’ ratio (2.36±0.70 vs. 2.11±0.71, p <0.01) with a greater early diastolic E’ (19.30±4.06 cm/sec vs. 18.18±4.05 cm/sec, p =0.02). Greater LVMI and lower heart rate were independent predictors of elite endurance athletes [odds ratio (OR) and 95% confidence intervals: 1.03 (1.02, 1.04) and 0.96 (0.95, 0.98), respectively]. Greater LVMI, lateral mitral E’/A’ ratio and right ventricular systolic pressure were independent predictors of elite strength athletes [OR: 1.03 (1.01, 1.05), 1.50 (1.06, 2.12) and 1.12 (1.05, 1.19), respectively]. Conclusions: Cardiac structural and functional characteristics differ between endurance and strength elite athletes. While greater LVMI predicts elite status in both groups of Asian athletes, consistent with findings from Western elite athletes, greater diastolic function and right ventricular systolic pressure characterize strength elite athletes, while lower heart rate at rest predicts endurance elite athletic status.